SHRIMP zircon and titanite U-Pb ages, Lu-Hf isotope signatures and geochemical constraints for ~2.56 Ga granitic magmatism in Western Dharwar Craton, Southern India: Evidence for short-lived Neoarchean episodic crustal growth? - Mohan, M.; Sarma, D.; McNaughton, Neal; Fletcher, Ian; Wilde, Simon; Siddiqui, M.; Rasmussen, Birger; Krapez, Bryan; Gregory, Courtney; Kamo, S. (Elsevier BV, 2014)
SHRIMP U-Pb zircon and titanite age data for granites adjacent to the Gadag greenstone belt (GGB) in the Western Dharwar Craton (WDC), India, establish the occurrence of voluminous ~2.56 Ga granitic magmatism and indicate the development and evolution of the GGB over a time span of ~70 m.y. These new data show that the GGB has an evolutionary history distinct from the Chitradurga greenstone belt (CGB) to the south, which was previously considered to be linked to that of the GGB, based on the continuity of lithological associations.Whole rock geochemical data indicate granites marginal to the GGB are potassic, were derived from intracrustal melting of an arc crust, without the involvement of mantle, and demonstrates the prevalence of horizontal tectonics in the evolution of Dharwar Craton. Lu-Hf zircon studies indicate that these rocks were derived from a heterogeneous arc-crust with distinct crustal histories on either side of the GGB. The voluminous ~2.56 Ga granitic magmatism surrounding the GGB in the WDC, in addition to the known ~2.61 and 2.56–2.52 Ga felsic magmatism supports a number of short-lived, episodic crustal growth events within the Dharwar Craton during the Neoarchean over a period of ~100 m.y. Short-lived episodic crustal growth during the Archean, typically within the time scale of few million years marks the distinction with long-lived modern-style subduction processes; these variations are often attributed to hotter Archean mantle and prevailing geodynamic regime.